Semiterrestrial crabs of the genus Geosesarma De Man, 1892 (Crustacea, Brachyura, Sesarmidae) from western Borneo, Indonesia, with descriptions of three new species - Ng, Peter K. L. (Zootaxa, 2015)
The poorly known semiterrestrial sesarmid crab, Geosesarma amphinome (De Man, 1899), from Kalimantan Barat in western Borneo, is redescribed and figured. Three other species from areas surrounding the town of Pontianak, are here described as new. Geosesarma ambawang sp. nov., G. pontianak sp. nov., and G. pylaemenes sp. nov. can be distinguished from congeners on Borneo and adjacent areas by their colours in life, form of the carapaces and ambulatory legs, and the structures of the male abdomens and first gonopods.